Formy negatywnego kultu religijnego w "Trylogii" Henryka Sienkiewicza - Kowalkiewicz, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2002)
The article touches upon a subject of the events and phenomena belonging to the circle of magic which is the art of performing tasks for beyond the abilities of an ordinary man. Thus, the article covers witches (why they appear in the novel), their prophesies as well as symbolic interpretations of these predictions. The manifestations of negative cult also include human belief in phantoms, evil spirits and even Satan himself. The introduction of such motifs to Trilogy reveals the author’s profound knowledge and broad interest in this subject. Natural curiosity about what the future will bring, aroused people's concern over all the phenomena occurring in nature. This theme is also a part of this study. The last part of this article covers the subject of various interpretations of the symbols of birds. It also ponders upon the motif of death and how it is portrayed in the novels by Henryk Sienkiewicz.